2015
DOI: 10.2217/epi.15.76
|View full text |Cite
|
Sign up to set email alerts
|

A Bivalent Role of TIP60 Histone Acetyl Transferase in Human Cancer

Abstract: Acetylation is a major modification that is required for gene regulation, genome maintenance and metabolism. A dysfunctional acetylation plays an important role in several diseases, including cancer. A group of enzymes-lysine acetyltransferases are responsible for this modification and act in regulation of transcription as cofactors and by acetylation of histones and other proteins. Tip60, a member of MYST family, is expressed ubiquitously and is the acetyltransferase catalytic subunit of human NuA4 complex. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 104 publications
2
47
0
2
Order By: Relevance
“…Previous studies have paradoxically characterized NuA4 as both a tumor suppressor and an oncogene (Gorrini et al 2007;Judes et al 2015). Maintenance of proper cell cycle gene expression may in part underlie some roles for NuA4 in cancer, while others may be due to its roles in DNA damage signaling (Squatrito et al 2006).…”
Section: Nua4 and Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have paradoxically characterized NuA4 as both a tumor suppressor and an oncogene (Gorrini et al 2007;Judes et al 2015). Maintenance of proper cell cycle gene expression may in part underlie some roles for NuA4 in cancer, while others may be due to its roles in DNA damage signaling (Squatrito et al 2006).…”
Section: Nua4 and Cancermentioning
confidence: 99%
“…However, the NuA4 complex also acts as an essential repressor of gene expression in certain contexts, such as embryonic stem cells (Fazzio et al 2008;Chen et al 2013), and can promote closed chromatin formation in flies (Qi et al 2006). Furthermore, NuA4 components paradoxically act as both tumor suppressors and oncogenes, leaving their positive vs. negative roles in cell cycle control unresolved (Sapountzi et al 2006;Judes et al 2015).…”
Section: The Nua4 Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Tip60 has been shown to remodel chromatin in several diseases, including several cancers such as lymphoma, melanoma, breast, colon, and lung cancer [28]. Many studies have shown that Tip60 may function as a tumor suppressor [29,30]. Hu et al reported that during the blastocyst stage of development, lack of Tip60 promoted embryo lethality, showing that Tip60 is an essential gene [31].…”
Section: Tip60 Attenuated the Proliferation And Metastasis Of Cca Celmentioning
confidence: 99%
“…Additionally, Tip60 played a role as a co-activator to interact with many steroid hormone receptors, such as the androgen receptor (AR) [15], that participate in the occurrence and development of prostate cancer. Other research indicated that Tip60 could facilitate AR acetylation to improve its transcriptional activity [16][17][18]. Furthermore, the expression of Tip60 was increased significantly in clinical prostate cancer tissues and castration-resistant prostate cancer cells, and its expression level was closely related with progression of the disease [19].…”
mentioning
confidence: 97%